Spectrofluorometric investigations on the solvent effects on the photocyclization reaction of diclofenac - Abdulilah Dawoud, Bani-Yaseen (2023)
The solvent effects on the photochemical conversion rate of the photosensitizing drug diclofenac (DCF) were investigated using steady-state fluorescence spectroscopy. The spectral information obtained for the photochemical reaction of DCF in a set of neat solvents demonstrates that the photoconversion reaction rate of DCF is not only medium polarity dependent but also hydrogen-bonding dependent. The solvent effects were qualitatively and quantitatively assessed employing various solvatochromic models, including multi-parameter linear regression analysis (MLRA). Interestingly, the MLRA results (R = 0.99) revealed that the photoconversion rate increases with increasing solvent polarizability (π*) and H-bond donor capability (α), whereas the rate decreases with increasing hydrogen-bond acceptor capability (β). However, predominant effect of the solvent acidity compared to basicity and polarizability was observed. A hypothesis rationalizing the effects of H-bonding and medium polarity on DCF photoconversion reaction is presented and discussed.